Guidelines in the discipline of Software Engineering Methodology - Cherednichenko, Olga Yuriivna; Shmatko, Oleksandr Vitaliyovych; Litvinova, Uliya Sergiivna; Sutyahin, Oleksandr Oleksandrovich (National Technical University "Kharkiv Polytechnic Institute", 2025)
The discipline "Software Engineering Methodology" plays a key role in the formation of highly qualified specialists capable of creating effective software solutions that meet modern standards. Software engineering methodology covers a wide range of methods, approaches and practices aimed at optimizing the entire software product life cycle - from requirements formulation and design to testing, deployment and subsequent support. Studying this discipline allows students to master not only the theoretical foundations, but also to gain practical skills in using modern technologies, tools and methodologies, such as Agile, Scrum, Kanban, DevOps, as well as quality-oriented development models (TDD, BDD). The methodological recommendations presented in this document are aimed at making the learning process as structured, consistent and close to the real needs of the industry as possible. The recommendations cover key concepts, ideas and methods in detail, and also provide examples of their application in real projects. The discipline is an important component of master's training, as it allows not only to deepen knowledge of the technical aspects of software development, but also to form a systemic vision of software project management, taking into account their technical, economic, organizational, and social aspects. The methodological recommendations can be used as a basic tool for teachers who teach the discipline, as well as for students who seek to master it independently. The document includes both theoretical material and practical tasks that will help consolidate knowledge and apply it in practice. Ultimately, its goal is to help students develop the necessary competencies for successful professional activity in the field of software development.
Keywords: guidelines; structure of the theoretical module; software development life cycles; software systems design methods; information technology; computer systems; reengineering of software systems